Rapid Ragi: A speed breeding protocol for finger millet - Sajja, Sobhan; Pranati, Jwala; Shyamala, S.; Vinutha, K.S.; Reddy, Ramya; Joshi, Priyanka; Pannem, Srinivasulu; Rakshit, P.; Jadhav, Yashoda; Kumar, C.V. Sameer; Mayes, Sean (Springer, 2025)
Background Climate change is gradually increasing demand for resilient, nutritious crops like finger millet or ragi. Ensuring food security requires researchers to develop improved and adapted cultivars rapidly. Modern techniques such as genomics-assisted breeding have emerged in the previous decade and combined with rapid generation advancement they will offer a step change in the speed of cultivar development.